Comparative Analysis of Antioxidant Vitamins, Minerals and Bioactive Compounds of Black Pepper (Piper guineense) Seed, Turmeric (Curcuma longa) and Ginger (Zingiber officinale)Rhizomes Spices - Okoye, Obiageli I.; Nwobi, Adaobi C.; Chukwuka, Oluebube F.; Agbo, Chinyere E; Ezeja, Enechojo P. (Journal of Home Economics Research, 2024)
The study compared antioxidant vitamins, minerals and bioactive compounds of three selected local spices (turmeric, African black pepper and ginger) consumed in Nigeria. Specifically, the study analysed the antioxidant vitamin (pro vitamin A, C, E), mineral (iron, copper, sodium potassium, manganese, zinc, magnesium) and phytochemical (steroid, tannin, glycoside) compositions. The samples were prepared for chemical analysis using reference standard methods. Data were analysed using mean and standard deviation. Analysis of variance was also used to test for differences. Results on antioxidant vitamins showed that pro vitamin A content of turmeric was significantly higher (322.24 μg /100g) compared to ginger (177.16μg/100g ) and black pepper (75.43μg/10g). Vitamin C content of ginger was significantly higher (27.73mg/100g) compared to black pepper (20.69mg/100g) and turmeric (20.62mg/100g). Magnesium content of black pepper was significantly higher (303.61mg/100g) than that of turmeric (241.0 mg/100g) and ginger (194.73 mg/100g). Calcium concentration of black pepper was significantly higher (357.67 mg/100g) compared to turmeric (167.67mg/100g) and ginger (162.00mg/100g). The iron content of the ginger was significantly higher (0.51mg/100g) compared to black pepper (0.34mg/100g) and turmeric (0.29mg/100g). Phytochemical analysis showed that steroid concentration in black pepper was significantly higher (1.80mg/100g) compared to turmeric (0.99mg/100g) and ginger (0.35mg/100g). The value of tannin in black pepper was significantly higher (6.27mg/100g) compared to turmeric (4.67mg/100g) and ginger (3.50mg/100g).